Neuroprotective Effect of Carotenoid-Rich Enteromorpha prolifera Extract via TrkB/Akt Pathway against Oxidative Stress in Hippocampal Neuronal Cells - Seung Yeon Baek; Mee Ree Kim (Marine Drugs, 2020)
In this study, we found that E. prolifera extract (EAEP) exhibits neuroprotective effects in oxidative stress-induced neuronal cells. EAEP improved cell viability as well as attenuated the formation of intracellular reactive oxygen species (ROS) and apoptotic bodies in glutamate-treated hippocampal neuronal cells (HT-22). Furthermore, EAEP improved the expression of brain-derived neurotrophic factor (BDNF) and antioxidant enzymes such as heme oxygenase-1 (HO-1), NAD(P)H quinine oxidoreductase-1 (NQO-1), and glutamate–cysteine ligase catalytic subunit (GCLC) via the tropomyosin-related kinase receptor B/ protein kinase B (TrkB/Akt) signaling pathway. In contrast, the pre-incubation of K252a, a TrkB inhibitor, or MK-2206, an Akt-selective inhibitor, ameliorated the neuroprotective effects of EAEP in oxidative stress-induced neuronal cells. These results suggest that EAEP protects neuronal cells against oxidative stress-induced apoptosis by upregulating the expression of BDNF and antioxidant enzymes via the activation of the TrkB/Akt pathway. In conclusion, such an effect of EAEP, which is rich in carotenoid-derived compounds, may justify its application as a food supplement in the prevention and treatment of neurodegenerative disorders.